On the brink: micromammals from the latest Villanyian from Bıçakçı (Anatolia). (28th January 2015) - van den Hoek Ostende, Lars W.; Diepeveen, Flemming; Tesakov, Alexey; Saraç, Gerçek; Mayhew, David; Alçiçek, M. Cihat; Donovan, Stephen K.; Stringer, Christopher B.
<x xml:space="preserve">Abstract</x> The locality of Bıçakçı (Çameli basin, Anatolia) has yielded a diverse fauna of micromammals. The arvicolines are the most diverse and abundant group. Their stage in evolution shows that the fauna is late Villanyian in age and can be placed in the lower part of the zone P of the Anatolian Neogene biozonation. Thus, it is on the brink of the important Villanyian/Biharian transition. The presence of three species of hamster, in combination with the occurrence of Borsodia, a high abundance of Kalymnomys and a near absence of insectivores, suggests a dry, open landscape. However, the important contribution of Clethrionomys in the vole fauna indicates the nearby presence of woodlands. Overall, the environment at the time of deposition appears to have been similar to that of the area today. Copyright © 2015 John Wiley & Sons, Ltd.